Extremely large, non-oxidized graphene flakes based on spontaneous solvent insertion into graphite intercalation compounds. (November 2018) - Kim, Jungmo; Yoon, Gabin; Kim, Jin; Yoon, Hyewon; Baek, Jinwook; Lee, Joong Hee; Kang, Kisuk; Jeon, Seokwoo
Abstract: Demand for an effective strategy for exfoliating layered materials into flakes without perturbing their intrinsic structure is growing. Herein, we introduce an effective fabrication method of large-sized non-oxidized graphene flakes (NOGFs) as a representative example of a general strategy using spontaneous insertion of exfoliating medium into a layered material. We fabricated a ternary graphite intercalation compound (t-GIC) with stoichiometry of KC24 (THF)2, and analyzed its morphology and electronic structure through experimental and computational approach. Interactions between the t-GIC and aprotic organic solvents with different polarities were investigated, where a unique swelling behavior was observed with dimethyl sulfoxide (DMSO). Based on the analysis of the phenomena, we demonstrate facile exfoliation of the t-GIC in polyvinyl pyrrolidone (PVP)-DMSO solution for fabrication of highly crystalline and large-sized NOGFs. The lateral size of the NOGFs ranges over 30 μm, while the 98% having thickness below 10 layers. The NOGF film exhibits supreme electrical conductivity of 3.36 × 10 5  S/m, which is, to our best knowledge, the highest value for a thin conductive film made of graphene flakes. Graphical abstract: Image 1